Concrete Surfacing Using Surface Energy of Nanoparticles - SychovÐ°, Anastasia; Svatovskaya, Larisa; Starchukov, Dmitriy; Gera, Vassily; Sychov, Maxim (International Journal of Engineering and Technology, 2018)
This article considers scientific and practical principles of concrete surfacing. As it was found, such production can be done by impregnating the surface of high-strength concrete with silica sol, measuring the surface energy of nanoparticles introduced. A technique was introduced for calculating surface energy of sols, so was the range of energy necessary to create concrete with a shock resistant surface, determined by measurement and calculation. The content contains possible reactions resulting in new phases in the concrete top during the impregnation with silica sol. Physical and mechanical characteristics of surfaced concrete were also outlined ad considered, so were the XRD data and electron microscopy data. Various types of energy used to surface concrete until high dynamic strength were compared. This article provides evidence that surface energy of sol nanoparticles can be considered as an independent alternative source.Â Â